Comparison of Spinal Manipulation Methods and Usual Medical Care for Acute and Subacute Low Back Pain. Issue 4 (15th February 2015) - Schneider, Michael; Haas, Mitchell; Glick, Ronald; Stevans, Joel; Landsittel, Doug
<x xml:space="preserve">Abstract</x> Study Design. Randomized controlled trial with follow-up to 6 months. Objective. This was a comparative effectiveness trial of manual-thrust manipulation (MTM) versus mechanical-assisted manipulation (MAM); and manipulation versus usual medical care (UMC). Summary of Background Data. Low back pain (LBP) is one of the most common conditions seen in primary care and physical medicine practice. MTM is a common treatment for LBP. Claims that MAM is an effective alternative to MTM have yet to be substantiated. There is also question about the effectiveness of manipulation in acute and subacute LBP compared with UMC. Methods. A total of 107 adults with onset of LBP within the past 12 weeks were randomized to 1 of 3 treatment groups: MTM, MAM, or UMC. Outcome measures included the Oswestry LBP Disability Index (0–100 scale) and numeric pain rating (0–10 scale). Participants in the manipulation groups were treated twice weekly during 4 weeks; subjects in UMC were seen for 3 visits during this time. Outcome measures were captured at baseline, 4 weeks, 3 months, and 6 months. Results. Linear regression showed a statistically significant advantage of MTM at 4 weeks compared with MAM (disability = −8.1, P = 0.009; pain = −1.4, P = 0.002) and UMC (disability = −6.5, P = 0.032; pain = −1.7, P < 0.001). Responder analysis, defined as 30% and 50% reductions in Oswestry LBP Disability Index scores revealed a significantly greater proportion of responders at 4 weeks in MTM (76%; 50%) compared with MAM (50%; 16%) and UMC (48%; 39%). Similar between-group results were found for pain: MTM (94%; 76%); MAM (69%; 47%); and UMC (56%; 41%). No statistically significant group differences were found between MAM and UMC, and for any comparison at 3 or 6 months. Conclusion. MTM provides greater short-term reductions in self-reported disability and pain scores compared with UMC or MAM. Level of Evidence: 2